(untitled) (Journal of Hama University, 2022)
The current research aimed to, know the level of each of the life skills and motivation for achievement among a sample of students of the faculty of education at Hama university and among students of the first and the fourth year, know the relationship of life skills to achievement motivation among the members of the total research sample. The research also aimed to know the differences between the score averages of the sample members in life skills and achievement motivation that belong to the variable of the academic year. The research sample consisted of (248) students among students of the faculty of education at Hama university,(61) students from the first year and (187) students from the fourth year. The researcher used a scale of life skills prepared by herself and a background scale (2006)for achievement motivation after doing the appropriate psychometric study for the two scales. The most important findings of the research were: the presence of an average level of life skills among the members of the total research sample in the total score of the scale and in its sub-dimensions, there is a low level of life skills among the first year students in the total score of the scale and its sub-dimensions, except for the fifth dimension (control and management of psychology) which was an average level. The level of life skills of the fourth year students was average in the total score and in the sub-dimensions of the scale as a whole.the presence of an average level of achievement motivation among the members of the total research sample in the total score of the scale and in its sub-dimension.the level of achievement motivation among the first year students was average in the total score of the scale and its first and second dimensions. The level was low in the third, the fourth and the fifth dimension. The level of achievement motivation was average among the fourth year students in the total score of the scale and in the its third ,fourth and fifth dimensions while the first and the second dimensions had a low level. there is a correlation between life skills and achievement motivation among the members of the total research sample.there are differences, between the score averages of the members of the sample in each of life skills and achievement motivation that belong to the variable of the academic year, for the benefit of the fourth year students.